Eternal Sunshine of the Spotless Mind - Butler, Andrew (BFI Film Classics Ser., 2014)
An instant cult classic, Michel Gondry's Eternal Sunshine of the Spotless Mind was both a critical and commercial success. Andrew M. Butler delves into the film's central themes and production processes, including the intertwined careers of Gondry and Kaufman, the film's various genres, its psychoanalytic aspects, and its debt to Philip K. Dick.
https://katalog.adlr.link/Record/0-177635754X